(untitled) (Proceedings of Voronezh State University. Series: Geology, 2023)
Introduction: As a result of the generalization of a huge amount of factual, literary, and analytical material on the geological structure, material composition and diamond content of the primary deposits of many ancient platforms of the world, the typing of primary diamond deposits was performed according to a set of characteristics, standard models of the diamond-bearing diatremes of the Siberian (SP), East European (EEP), South African (SAA) and Australian (AuP) platforms. Based on the peculiarities of the geological and tectonic position of individual groups of kimberlites, their mineralogical and petrographic characteristics, petrochemistry, age, crystal and morphological types of diamonds and diamond content, significant differences are noted between the original and transformed rocks in diatremes. Objects, methods, results and discussion: Among the secondary formations of kimberlite rocks of the ancient platforms of the world, sulphide minerals are quite widespread, among the dominant role belongs to pyrite. In addition to ferruginous varieties, sulphides of other metals were also noted. In kimberlites of the Siberian Platform (SP), pyrite forms both continuous masses and aggregates, as well as individual crystals and their druses, which are most characteristic of the upper horizons of diatremes, affected to varying degrees by weathering processes. Pyrite was also noted on the deeper horizons of the pipes in zones influenced by highly mineralized hydrogen sulphide solutions, which introduced various elements into the kimberlite environment, including sulphur, which easily combines with iron released by various changing minerals. The reasons for the co-occurrence of various minerals with different habit forms of pyrite can be different: temperature changes, changes in the concentration of iron, hydrogen, hydrogen sulphide and other ions. Sphalerite noted in the upper parts of many SP diatremes, associated with other sulphides. Together with calcite, the mineral was found in individual veins and at the deep horizons of a number of diatremes. Most often, the mineral composes continuous masses and irregularly shaped segregations in altered kimberlites. Galena was revealed in small quantities only in the upper parts of individual pipes in association with other minerals. Sometimes it was noted on the walls of cracks, forming euhedral crystals of tetrahedral habit. Several morphological forms of the mineral have been established: a) octahedral with the subordinate development of a cube and a rhombic dodecahedron; b) cubic with subordinate faces of the octahedron and rhombic dodecahedron; c) cuboctahedral. Millerite in kimberlites was found as an impurity in newly formed sulphides. Pyrrhotite in kimberlites develops along small cracks in the form of fine-grained small aggregates in calcite, as well as scattered grains in the bulk of the rocks. Tochilinite was found in many kimberlite pipes in association with other minerals. Marcasite was found both in the bulk of rocks and in the form of veins and borders on other new formations. Chalcopyrite also was revealed in the upper parts of the diatremes. The quantitative contents and relationships of various sulphides significantly affected the magnetic and petrophysical properties of rocks, which should be taken into account when prospecting for diamonds. Conclusions: The bulk of pyrite in kimberlites was deposited before the precipitation of calcite, but some of it crystallizes together with calcite, and also after the growth of the latter ceases. Pyrite crystals of cubic and octahedral habit occur in the same druse, and their age relationships are not always clear. The formation of sulphides probably currently takes place, since the contamination of fractured waters with hydrogen sulphide in some diatremes is quite high. Sulphides were also released during the hydrothermal stage at fairly high temperatures. Proof of this are the inclusions of pyrite in amethyst. The main source of sulphur for sulphides was the Precambrian and Lower Paleozoic sedimentary strata hosting kimberlite diatremes, the fissure waters of which (as well as highly mineralized aqueous solutions) were enriched with hydrogen sulphide.